2020
DOI: 10.28991/scimedj-2020-0202-3
|View full text |Cite
|
Sign up to set email alerts
|

PET-CT and Occupational Exposure in Oncological Patients

Abstract: The paper describes the results of retrospective epidemiological study on low dose effects of diagnostic radiation exposure to humans. The data used in the study has been collected from archives of Chelyabinsk Regional Clinical Center of Oncology and Nuclear Medicine during the project for creating the local electronic database of Ozyorsk patients examined with computed tomography (CTDB). The study group consisted of oncological patients who have received positron-emission computed tomography (PET-CT). All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…The number and dose of CT studies are one of the largest sources of imaging exposure. A typical chest CT scanning delivers a dose of 4–7 mSv to the patient [ 18 ], and it raises the risk of cancer incidence and mortality [ 19 , 20 ]. Thus, although CT scan has played an important role in the management of COVID-19-infected patients, it can promote malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…The number and dose of CT studies are one of the largest sources of imaging exposure. A typical chest CT scanning delivers a dose of 4–7 mSv to the patient [ 18 ], and it raises the risk of cancer incidence and mortality [ 19 , 20 ]. Thus, although CT scan has played an important role in the management of COVID-19-infected patients, it can promote malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Also, anthropomorphic phantoms of the head and neck can be used for CT scans, which reduce radiation risk while maintaining image quality. [ 44 ] However, in the study by Osipov et al, [ 45 ] diagnostic exposure of PET-CT did not reveal significant effect on mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, logistic issues like scanning time in an active PET service and the extra brain scanning time will reduce the overall number of patients scanned per day [19]. Radiation exposure could be considered a downside of the discussed modality; however, Osipov et al showed that diagnostic exposure due to repeated PET-CT examinations in a group of oncological patients was not associated with changes in mortality [47]. Reduced kilovolts (kVs) with automatic exposure control were a suggested attempt to optimize the radiation exposure in head and neck scans [48].…”
Section: Discussionmentioning
confidence: 99%